Murilo Mendes assimilates poetry - Infante, Ulisses (2016)
Murilo Mendes says in autobiographical texts that he was a careful reader of poems. Thus his memory was peopled by a large collection of images and references, many of which the poet distributed in several of his poems . Tracking the presence of this extraneous matter in the poetry of Murilo is a way of picking up his interpretations and the possibilities of expression he detected and assimilated. Also, it is possible to realize the poetical composition processes based on the embedded images and rhythmic units redefinition. The corpus of poems and texts analyzed in this paper aims to show how the incorporation – etymologically "junction", "bundling" – of other poets’ matter allowed Murilo Mendes to ponder the poet's role in modernity -- among other themes.